Measurement of signal-to-noise ratio (SNR) in off-axis particle holography using paraxial approximation - TAMRIN, K. F. (2014)
Particle image velocimetry (PIV) technique in its original form is limited to in-plane two-dimensional two-component (2D-2C) displacement and velocity measurements. Although it is possible to extract the out-of-plane component through stereoscopic viewing, the useful measurement volume remains limited to a light sheet of several millimeters thick. On the other hand, integration of holographic recording in PIV (HPIV) has finally realised whole-field, three-dimensional three-component (3D-3C) displacement and velocity measurements. In comparison to in-line particle holography, off-axis particle holography offers a relatively higher signal-to-noise ratio (SNR) although it demands long coherence and high laser energy for flow diagnostics. In-line particle holography relaxes the requirements of such a system but at the expense of image (signal) degradation due to superposition of virtual image waves, the directly transmitted reconstruction wave and the real image. On this basis, off-axis setup is favourable, as in theory, the only influencing noise is the out-of-focus real images. This paper introduces a new approach of SNR analysis which considers the position of out-of-focus real images based on the paraxial approximation to spherical wavefronts. It was shown that the formulated off-axis SNR agrees well with other established expressions found in the literature. The SNR was shown dependent on particle number density, square of particle diameter and depth volume.